An Aging Study of NCA/Si-Graphite Lithium-Ion Cells for Off-Grid Photovoltaic Systems in Bolivia. Issue 10 (29th October 2021) - Benavente-Araoz, Fabian; Ko, Jing Ying; Lundblad, Anders; Ekström, Henrik; Lindbergh, Göran
Abstract : Performance and aging of lithium-ion 18650 cylindrical cells containing NCA and Si-graphite composite electrodes are investigated during long-term low current rate (∼0.1C) cycling protocol resembling charge/discharge profile of off-grid photovoltaic battery system. The cells are cycled within 30% and 75% state-of-charge ranges (∆SOC) with low, middle and high cut-off voltages. Electrochemical impedance spectroscopy data of full cylindrical cells exhibit severe aging for cells that have been cycled at higher cut-off voltage of 4.2 V. Symmetric cell impedance from each electrode shows that aging of NCA is dominant over aging of Si-graphite. Using a Newman-based impedance model, the NCA symmetrical cells' impedance spectra are parameterized to evaluate the aging modes. The resulting parameterization confirms increased particles' surface film resistance due to possible electrolyte oxidation and tortuosity increase at high cut-off voltages. Cycling the cells with middle and low cut-off voltages causes few significant changes when compared to calendar-aged samples. This opens up the possibility to significantly increase battery lifetime for small photovoltaic battery systems in rural areas of Bolivia.